In vitro propagation of the aromatic herb Strobilanthes tonkinensis Lindau - Srikun, Niyomsri (Agriculture and Natural Resources, 2017)
Strobilanthes tonkinensis Lindau is a rare aromatic herb belonging to the family Acanthaceae. Its plant extract has been confirmed as a major source of squalene. In this research, a protocol for micropropagation was developed that can support ex situ conservation and will benefit plant material production. Shoot explants were provided from plants grown in the greenhouse and trickle irrigated for 1 mth and then effectively sterilized by shaking in NaOCl at a concentration of 1.2% for 10 min, followed by 0.6% for 15 min, which produced 70% good-growing, healthy shoots. Increasing thidiazuron and N6-benzyladenine (BA) concentrations did not promote shoot multiplication. Shoot multiplication was the best on Murashige and Skoog (MS) medium supplemented with 16 µM BA. The highest shoot number (12 shoots/explant) was obtained at 8 wk of culture. The highest shoot elongation was obtained on the medium added with 16 µM BA for 4 wk and subsequent subculturing to hormone-free MS medium for another 4 wk. High frequency rooting (21 roots/shoot) was obtained on MS medium fortified with 7.5 µM indole-3-butyric acid. Complete plantlets that were transferred to pots under greenhouse conditions produced healthy plants with 100% survival after 5 wk.